The determinants of net interest margin (NIM) in the Sri Lanka banking system - Jayasena, D. M.; Winai Wongsurawat; Badir, Yuosre; Sununta Siengthai; Asian Development Bank - Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
This research study investigatethe determinants factors of bank Net Interest Margin (NIM) in Sri Lanka using a sample of 103 bank observation over the period from 1999 to 2008. Our empirical results proved that high operations cost in the domestic banks, credit risk measured by capital to assets ratio, absence of competition, and less diversified income sources are the main contributing factors. Further market interest rate negatively relates with bank interest margin and it shows that deposit rates of the banking sector in Sri Lanka are more sensitive to the falling interest rates. Further, ownership of the bank and opportunity cost measured by liquidity assets to total assets ratio are insignificant. Even though bank concentration ratio is insignificant in the model, still Sri Lankan commercial banks use their individual market power for pricing decisions.
A research study submitted in partial fulfillment of the requirements for thedegreeof Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2010
Keywords: Interest rates -- Sri Lanka